FDG-PET/CT Incidental Detection of Cancer in Patients Investigated for Infective Endocarditis - Gouriet, Frédérique; Tissot-Dupont, Hervé; Casalta, Jean-Paul; Hubert, Sandrine; Cammilleri, Serge; Riberi, Alberto; Lepidi, Hubert; Habib, Gilbert; Raoult, Didier (Frontiers in Medicine, 2020)
Background: Fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) is an imaging technique largely used in the management of infective endocarditis and in the detection and staging of cancer. We evaluate our experience of incidental cancer detection by PET/CT during IE investigations and follow-up. Methods and Findings: Between 2009 and 2018, our center, which includes an “endocarditis team,” managed 750 patients with IE in a prospective cohort. PET/CT became available in 2011 and was performed in 451 patients. Incidental diagnosis of cancer by PET/CT was observed in 36 patients and confirmed in 34 of them (7.5%) (colorectal n = 17; lung n = 7; lymphoma n = 2; melanoma n = 2; ovarian n = 2; prostate n = 1; bladder n = 1; ear, nose, and throat n = 1; brain n = 1). A significant association has been found between colorectal cancer and Streptococcus gallolyticus and/or Enterococcus faecalis [12/26 vs. 6/33 for other cancers, p = 0.025, odds ratio = 3.86 (1.19–12.47)]. Two patients had a negative PET/CT (a colon cancer and a bladder cancer), and two patients, with positive PET/CT, had a benign colorectal tumor. PET/CT had a sensitivity of 94–100% for the diagnosis of cancer in this patient. Conclusions: Whole-body PET/CT confirmed the high incidence of cancer in patients with IE and could now be proposed in these cases.